2018
DOI: 10.1101/278499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal PCP protein dynamics coordinate cell intercalation during neural tube closure

Abstract: Planar cell polarity (PCP) controls the convergent extension cell movements that drive axis elongation in all vertebrates. Though asymmetric localization of core PCP proteins is central to their function, we currently understand little about PCP protein localization as it relates to the subcellular behaviors that drive convergent extension. Here, we have used high magnification time-lapse imaging to simultaneously monitor cell intercalation behaviors and the localization of the PCP proteins Prickle2 and Vangl2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 61 publications
(84 reference statements)
2
9
0
Order By: Relevance
“…Our data also provide important new insights into the function of PCP signaling in vertebrate CE, which is an important issue given the implication of PCP genes in human neural tube defects (Wallingford et al, 2013). These results here are consistent patterns we observed recently in neural epithelial cells (Butler and Wallingford, 2018), which again is significant for demonstrating that the dynamic spatial and temporal patterns of Pk2 localization are conserved across cell fate (ectoderm vs. mesoderm) and tissue type (epithelial and mesenchymal). These results are also consistent with findings that anteroposterior patterning is central to the organization of CE in both Drosophila and Xenopus (Paré et al, 2014, Ninomiya et al, 2004, Zallen and Wieschaus, 2004.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our data also provide important new insights into the function of PCP signaling in vertebrate CE, which is an important issue given the implication of PCP genes in human neural tube defects (Wallingford et al, 2013). These results here are consistent patterns we observed recently in neural epithelial cells (Butler and Wallingford, 2018), which again is significant for demonstrating that the dynamic spatial and temporal patterns of Pk2 localization are conserved across cell fate (ectoderm vs. mesoderm) and tissue type (epithelial and mesenchymal). These results are also consistent with findings that anteroposterior patterning is central to the organization of CE in both Drosophila and Xenopus (Paré et al, 2014, Ninomiya et al, 2004, Zallen and Wieschaus, 2004.…”
Section: Discussionsupporting
confidence: 91%
“…We knocked down Pk2 using an antisense morpholino-oligonucleotide that has been validated in both convergent extension and polarization of multiciliated cells Wallingford, 2018, Butler andWallingford, 2015). Pk2 knockdown strongly disrupted both the elongation and the planar orientation of cells in the dorsal mesoderm, consistent with disruption of other core PCP proteins in dorsal gastrula mesoderm (Jessen et al, 2002, Wallingford et al, 2000( Figures 4A-4D).…”
Section: Prickle2 Controls the Frequency Of Actomyosin Oscillationsmentioning
confidence: 61%
See 2 more Smart Citations
“…To explore the molecular control of these oscillations, we turned our attention to the PCP signaling network, which has been implicated in control of both deep and superficial actomyosin dynamics in the dorsal mesoderm (Kim and Davidson, 2011) (Shindo and Wallingford, 2014). In addition, we recently showed that the core PCP protein Pk2 controls CE in neural epithelial cells, where it displays a tight temporal and spatial correlation with actomyosin at shrinking junctions (Butler and Wallingford, 2018). We therefore used mosaic expression to generate labeled cells that were directly apposed to unlabeled cells in the dorsal mesoderm ( Figure 3A).…”
Section: Prickle Displays Both Spatial and Temporal Patterns Of Localmentioning
confidence: 99%